Myosin heavy chain messenger RNA and protein isoform transitions during cardiac hypertrophy. Interaction between hemodynamic and thyroid hormone-induced signals. - Izumo, S (1987)
Expression of the cardiac myosin isozymes is regulated during development, by hormonal stimuli and hemodynamic load. In this study, the levels of expression of the two isoforms (alpha and beta) of myosin heavy chain (MHC) during cardiac hypertrophy were investigated at the messenger RNA (mRNA) and protein levels. In normal control and sham-operated rats, the alpha-MHC mRNA predominated in the ventricular myocardium. In response to aortic coarctation, there was a rapid induction of the beta-MHC mRNA followed by the appearance of comparable levels of the beta-MHC protein in parallel to an increase in the left ventricular weight. Administration of thyroxine to coarctated animals caused a rapid deinduction of beta-MHC and induction of alpha-MHC, both at the mRNA and protein levels, despite progression of left ventricular hypertrophy. These results suggest that the MHC isozyme transition during hemodynamic overload is mainly regulated by pretranslational mechanisms, and that a complex interplay exists between hemodynamic and hormonal stimuli in MHC gene expression.